Cutting efficiency of diamond burs operated with electric high‐speed dental handpiece on zirconia. (28th August 2015) - Nakamura, Keisuke; Katsuda, Yusuke; Ankyu, Shuhei; Harada, Akio; Tenkumo, Taichi; Kanno, Taro; Niwano, Yoshimi; Egusa, Hiroshi; Milleding, Percy; Örtengren, Ulf
<x xml:space="preserve">Abstract</x> Zirconia‐based dental restorations are becoming used more commonly. However, limited attention has been given to the difficulties experienced, concerning cutting, in removing the restorations when needed. The aim of the present study was to compare the cutting efficiency of diamond burs, operated using an electric high‐speed dental handpiece, on zirconia (Zir) with those on lithium disilicate glass–ceramic (LD) and leucite glass–ceramic (L). In addition, evaluation of the cutting efficiency of diamond burs on Zir of different thicknesses was performed. Specimens of Zir were prepared with thicknesses of 0.5, 1.0, 2.0, and 4.0 mm, and specimens of LD and L were prepared with a thickness of 1.0 mm. Cutting tests were performed using diamond burs with super coarse (SC) and coarse (C) grains. The handpiece was operated at 150, 000 rpm with a cutting force of 0.9 N. The results demonstrated that cutting of Zir took about 1.5‐ and 7‐fold longer than cutting of LD and L, respectively. The SC grains showed significantly higher cutting efficiency on Zir than the C grains. However, when the thickness of Zir increased, the cutting depth was significantly decreased. As it is suggested that cutting of zirconia is time consuming, this should be taken into consideration in advance when working with zirconia restorations.